1992
DOI: 10.1063/1.1142831
|View full text |Cite
|
Sign up to set email alerts
|

Cesium catalysis effect of H− ion production in volume production type of H− ion source

Abstract: The cesium catalysis effect of H− ion production in a volume production type of H− ion source has been investigated by the authors. These investigations suggest that the beam current enhancement is caused by a surface H− ion production process at the cesium covered plasma electrode. In order to examine this process in detail, measurement of the H− ion production probability by scattering thermal hydrogen atoms from a cesium covered molybdenum surface has been made. The measured H− ion production probability ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…193 Production of H À ions by injecting thermal H atoms to low work function surface was later confirmed by Lee and Seidl 194 and by Okuyama and Mori. 195 Yu experimentally investigated surface production of H À by ion bombardment induced hydrogen desorption, or sputtering of adsorbed hydrogen on the surface. 196 He showed that the H À ion yield exhibited dependence upon work function resembling electron tunneling effect.…”
Section: B Theoretical Work On H 2 Surface Productionmentioning
confidence: 99%
“…193 Production of H À ions by injecting thermal H atoms to low work function surface was later confirmed by Lee and Seidl 194 and by Okuyama and Mori. 195 Yu experimentally investigated surface production of H À by ion bombardment induced hydrogen desorption, or sputtering of adsorbed hydrogen on the surface. 196 He showed that the H À ion yield exhibited dependence upon work function resembling electron tunneling effect.…”
Section: B Theoretical Work On H 2 Surface Productionmentioning
confidence: 99%
“…When grown to stationary-phase at 40~C or at 20°C, M)'cobacterildm hut)'ricldn! changes mainly the fatty acyl contents of cardiolipins [478] (Table II) Ester-linked fatty acyl phospholipids are in plasma membran,:s of eubactcrial thcrmophilcs that remain stable at high temperatures, as do membranes with ether-linked phytanyl glycerols in arehaebacterial thermophilcs. The eubacterial moderate thermophilc Bacillus stearothermophilus grows optimally at 65°C, the extreme thermophile Thermophilus aquaticus, at 90°C.…”
Section: Ri-o-c H E R-o-t:h H~c-o-p-o-c Hzmentioning
confidence: 99%
“…15 and compared with the experimental result. 16 The H − ion production rate monotonically increases with the H 0 atom energy. Thus, the energy relaxation process of the H 0 atom is important for the H − ion production.…”
Section: B Simulation Model For H 0 Atom Transportmentioning
confidence: 98%